(untitled) (Homoeopathy for All, 2024)
Fungal infections are caused by various species of fungi that can invade and infect various parts of the human body, from superficial layers like skin and mucous membranes to deeper tissues and organs. While some fungal infections remain mild and can resolve with minimal intervention, certain infections become severe and even life-threatening, especially in individuals with weakened immune systems. Fungi that lead to human infections often act as opportunistic pathogens, taking advantage of the host’s compromised immunity to cause disease. These infections can range from common conditions like athlete’s foot and ringworm to more serious infections like Aspergillosis and Candidiasis, especially in those with underlying health issues.